Answer:
First option
Step-by-step explanation:
The result of first expression:
7(6+z) multiply 7 with inside the parenthesis
7(6+z) = 42 + 7z
the result of second expression:
since we need to do multiplying first,
7*6 = 42 and 7*z = 7z
then we add them
42 + 7z this is the same result we found for the first equation
Answer:
1
Step-by-step explanation:
y2 - y1/ x2 - x1
3-2/ 5-4 = 1/1 = 1
If my answer is incorrect, pls correct me!
If you like my answer and explanation, mark me as brainliest!
-Chetan K
<h3>
♫ - - - - - - - - - - - - - - - ~<u>
Hello There</u>
!~ - - - - - - - - - - - - - - - ♫</h3>
➷ The correct number sentence is D. 5.5 + (-2.5) = 3.0
<h3><u>
✽</u></h3>
➶ Hope This Helps You!
➶ Good Luck (:
➶ Have A Great Day ^-^
↬ ʜᴀɴɴᴀʜ ♡
Answer:
Step-by-step explanation:
the formula for circumference of a circle is 2 x pi x r(radius).